OPC Protocol Application for Real-Time Carbon Monitoring System for Industrial Environment - Mohd Faiz Rohani; Noor Azurati Ahmad; Shamsul Sahibuddin; Salwani Mohd Daud (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Global warming is referred to the rise in average surface temperatures on earth primarily due to the Greenhouse Gases (GHG) emissions such as Carbon Dioxide (CO2). Monitoring the emissions, either direct or indirect from the industrial processes, is important to control or to minimize their impact on the environment. Most of the existing environmental monitoring system is being designed and developed for normal environment monitoring. Hence, the aim of this project is to develop industrial CO2 emission monitoring system which implements industrial Open Platform Communications (OPC) protocol in an embedded microcontroller. The software algorithm based on OPC data format has been designed and programmed into the Arduino microcontroller to interface the sensor data to any existing industrial OPC compliant Supervisory Control and Data Acquisition (SCADA) system. The system has been successfully tested in a lab with the suitable environment for real-time CO2 emissions measurement. The real-time measurement data has been shown in an industrial SCADA application which indicates successful implementation of the OPC communications protocol.